GROWTH AND PRODUCTION OF Paspalum notatum cv. Competidor IN VARIOUS COMBINATION ON DIFFERENT LEVEL OF N, P, AND Ca FERTILIZER. - B. M. M, Stephanie; Partama, I. B. G.; Wirawan, I W. (Jurnal Peternakan Tropika, 2018)
The purpose of this research is to find out the effect about growth and production of Paspalum notatum cv. competidor in various combination at different level of N, P, and Ca fertilizer. This research was conducted for 12 weeks at Greenhouse, Research Station of Animal Husbandry Faculty, Udayana University, Denpasar. This research is designed by Completely Randomized Design (CRD) with 10 treatments combination and 3 repeatements, so there were 30 pots of experimental unit with various combinantion fertilizer. The treatments combination was consist: control or without any fertilizer involved; 100, 150, 200 kg/ha of N fertilizer; 50, 100 kg/ha of P fertilizer, and 50, 100 kg/ha of Ca fertilizer in certain combination has been designed. Variable observed were plant length, number of leaf, number of branches, leaf dry weight, branches dry weight, total foarage dry weight, ratio of leaf dry weight and branches dry weight, leaf area, and the last chlorophyle content. According to the result of this research is showed that all of variables have significant result based on statistic test (P < 0,05) unless plant length and chlorophyle content showed non significant result  (P > 0,05) based on statistic test. According to this research, combination of fertilize N 150 P 50 Ca 50 is giving the best result based on all of observed variable. Keyword: Paspalum notatum cv. Competidor, combination of fertilizer ,  fertilizer of N, P, Ca